High-Performance Computing of Self-Gravity for Small Solar System Bodies. - Frascarelli, Daniel; Nesmachnow, Sergio; Tancredi, Gonzalo (Computer (00189162), 2014)
To study the evolution of small solar system bodies like asteroids and comets, a fast method is needed to compute the self-gravity of systems composed of millions of particles. A proposed fully parallel shared-memory algorithm for dense, self-gravitating agglomerates scales efficiently with the number of particles as well as the number of computational resources.